2017
DOI: 10.4049/jimmunol.1700223
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Mediated Inflammation in Normal and Diabetic Wound Healing

Abstract: The healing of cutaneous wounds is dependent on the progression through distinct, yet overlapping phases of wound healing, including hemostasis, inflammation, proliferation, and resolution/remodeling. The failure of these phases to occur in a timely, progressive fashion promotes pathologic wound healing. The macrophage (MΦ) has been demonstrated to play a critical role in the inflammatory phase of tissue repair, where its dynamic plasticity allows this cell to mediate both tissue-destructive and -reparative fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
330
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(342 citation statements)
references
References 113 publications
(132 reference statements)
4
330
2
6
Order By: Relevance
“…Emerging evidence suggests that macrophage dysfunction is a component of the pathogenesis of nonhealing and poorly healing wounds (25,27). In addition, extensive research has reported that macrophage accumulation is observed in patients with diabetes and plays an important role in wound healing (13,28). In individuals with type 2 diabetes, a study sustained the notion that inflammasome activity in macrophages impairs wound healing and a significantly higher number of macrophages are present in the edge of both types of chronic ulcer (diabetic wounds and venous ulcers) (29).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that macrophage dysfunction is a component of the pathogenesis of nonhealing and poorly healing wounds (25,27). In addition, extensive research has reported that macrophage accumulation is observed in patients with diabetes and plays an important role in wound healing (13,28). In individuals with type 2 diabetes, a study sustained the notion that inflammasome activity in macrophages impairs wound healing and a significantly higher number of macrophages are present in the edge of both types of chronic ulcer (diabetic wounds and venous ulcers) (29).…”
Section: Discussionmentioning
confidence: 99%
“…A group of new strategies have been developed to promote the healing of these wounds, although the outcome is still not satisfactory (Alavi et al, 2014). Macrophage polarization plays critical roles in the wound healing process (Ferrante and Leibovich, 2012;Novak and Koh, 2013;Boniakowski et al, 2017). Therefore, clarifying the events of macrophage phenotype switching in bacterium-infected diabetic wounds is helpful for understanding the etiology of non-healing diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of Mo/MΦ that accumulate in skin wounds are thought to derive from circulating blood Mo in mice . Mo are produced in bone marrow by sequential differentiation from hematopoietic stem cells, under the control of a variety of growth factors and transcription factors .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue damage also results in increased bone marrow monopoiesis, which helps to supply Mo for tissue repair and to repopulate bone marrow and blood stores . Although most Mo/MΦ in skin wounds are thought to be derived from bone marrow Mo, a small population of skin resident MΦ also likely act as first responders upon wounding, contributing to the initiation of inflammation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation